Hubungan Teman Sebaya dan Peraturan Remaja Dengan Tindakan Kesehatan Reproduksi Remaja Dalam Pergaulan Dengan Lawan Jenis di SMAN 1 Arjasa - Raivi, Aan (Infokes, 2017)
Adolescent is a period of transition that must be passed all childhood to adulthood. Many things happen in this phase, adolescents who successfully passed the transition phase will determine the success undergo adult stage. This study focuses on one issue, namely the adolescent reproductive health triad as adolescent sexuality, premarital sexual behavior resulting in the risk of unwanted pregnancy. Taboo of sex education to students area needs communication, information, and education with true, appropriate, and effective that peer educator with simultaneous for the studens area and important to reproduction health information, early marriage and risk it, premarital sexual and risk it for communication, information, and education in integral to tackling early marriage happened. Purpose the purpose of this study was to relationships of peers and adolescent rules with adolescent reproductive health measures in association with the opposite sex. Methods is this study was an experimental study, the type of study design pre experiment one group pretest posttest design. Technique sampling is total sampling. The population in this study were 622 students with a sample of 208 students in second class SMAN 1 Arjasa. Results: Data analysis was performed using Wilcoxon signed rank test test with significance level of p ˂ α = 0:05. Results from this study is p value of 0.010 with α = 0.05%, and p value of 0.000 with α = 0.05%. Discussion The better the rules applied in school the better the action of adolescents in the association with the opposite sex, the better the rules applied by the parents at home, the better the teenagers will act in association with the opposite sex, and the better the influence of peers then the better the action of adolescents in the association with friends of the opposite sex. Conclusions: behavior effected to school rules, parents at home rule, and peers.